Throughput Analysis of Multicast Scheduling Algorithms by Varying NxN IQ Switch - Jumlesha, Shaik; Navaz, K; Athinarayanan, S (International Journal of Computer Sciences and Engineering, 2025)
Incredible measures of exertion have gone into investigate on multicast switch texture outline and calculations. Switch measure is one of the primary factor which impacts the execution of throughput and deferral. In this work, execution of switch has been investigated by applying the progressed multicast planning calculation OQSMS (Optimal Queue Selection Based Multicast Scheduling Algorithm), due date based round-robin booking calculation MDDR(Multicast Due Date Round Robin) and double round-robin based multicast planning calculation MDRR(Multicast Dual Round Robin). Recreation results demonstrate that OQSMS accomplishes preferred exchanging execution over different calculations under the allowable movement conditions on the grounds that if the switch measure builds, OQSMS will gauge ideal line determination in view of more line mixes so it accomplishes greatest conceivable throughput.